SCHOOL GAMES OF VACARIA CITY: ANALYSIS OF STUDENTS PARTICIPATION - Uilian Maciel Almeida; Gerard Maurício Martins Fonseca (Universidade Estadual do Oeste do Paraná, 2013)
The sports school games competitions are important the learning of social, cognitive and cultural aspects, being able to produce benefits to the education combined with development of sports in school. The aim of this article was to analyze the participation and distribution of students in relation to gender, male or female in those sports modalities in three editions of the games in the city of Vacaria-RS. We analyzed the enrollment of students from each school participating in the State School Games of Rio Grande do Sul (JERGS), from 2009 to 2011. 20 public schools have participated of the games, with elementary school students in the childrens category, ages between 13 and 14. Were occupied 2,307 places, filled by 1,123 students, being 794 male students and 329 female. It is noticed that students occupy places in more than one sport often and also noticed that boys have more participation than the girls. Through the Chi-square test it was detected significant differences (p0.05) when comparing the years of participation. Likewise, the test showed a difference in the larger participation of boys compared to girls (p0,05). The statistical analysis also pointed out that the sport had largest student participation was indoor soccer. We conclude that the current format of the competition does not provide an increase in the number of young participants over time and does not stimulate female participation.